近十五年(2009-2024)继承语研究动态及其发展趋势 - Chili Li; Yue Jiang; Yijie Wang; Shuang Zhang (Sinolingua: Journal of Chinese Studies, 2025)
With the development of globalization, exchanges between countries in the political, economic and cultural fields have increased. Immigrant families in the world will use heritage languages to maintain and pass on their cultural identities, making society develop towards diversification. In view of the upsurge in heritage language research in recent years, it is necessary to sort out the research dynamics and development trends in this field. Based on the CNKI database, this paper collected 46 relevant literatures on heritage language research from 2009 to2024, adopted a scoping review method, and used tools such as CiteSpace and Excel to sort out its development status and trends. The study found that: 1) The research on heritage language has gradually increased, especially reaching a peak in 2023, showing its attention in the academic community; 2) The research revealed many hot topics, including the language acquisition and development of heritage language, the identity and motivation research of heritage language learners, the policy support for the heritage language, and the impact of the social language environment on heritage language; 3) Taking 2015 and 2020 as the nodes, the research can be divided into three stages: the starting stage, preliminary exploration and rapid development; 4) The sudden increase in keywords such as heritage language, identity, and family reflects the changes in the attention of the academic community to heritage language, which may have a profound impact on education, policy and social culture.